The Theoretical Description for Paracetamol and Naproxen Electrochemical Determination, Assisted by Conducting Polymer Composite with Cobalt (III) Oxyhydroxide. - Lyudmyla V. Romaniv (Letters in Applied NanoBioScience. Vol. 13 No. 1, 2024. Р. 1-9., 2024)
naproxen; paracetamol; cobalt (III) oxyhydroxide; conducting polymers; electrochemical sensors; electrochemical oscillations; stable steady-state
Keywords: naproxen; paracetamol; cobalt (III) oxyhydroxide; conducting polymers; electrochemical sensors; electrochemical oscillations; stable steady-state